Thermostimulated luminescence spectra of InxTl₁-xI nanostructures synthesized in porous silicon - Franiv, A.V.; Bovgyra, O.V.; Savchyn, O.V. (Functional Materials, 2004)
The dose dependence of integral intensity of thermostimulated luminescence spectra of InxTl₁-xI nanostructures synthesized in porous silicon voids and exposed to hard y-radiation has been investigated. The mechanisms of recombination processes and the practical application possibility of the structures obtained as detectors of radioactive irradiation have been discussed.